Clinical Variables Associated with Quality of Life Among Women with Breast Cancer: A Cross-Sectional Study - Anna, Anastasia; Trisyani , Yanny; Nuraeni, Aan; Priambodo, Ayu Prawesti; Sugiharto, Firman (Journal of Applied Nursing and Health, 2026)
Background: Breast cancer is a major public health concern in Indonesia. Clinical factors such as disease duration, cancer stage, treatment type, and comorbidities may affect patients’ quality of life (QoL), but evidence in Indonesia remains limited. This study aimed to examine the correlation between clinical variables and QoL among breast cancer patients. Methods: This cross-sectional study was conducted between November 2025 and January 2026 at a referral hospital in West Java, Indonesia, and followed the STROBE guidelines. A total of 53 breast cancer patients were recruited using convenience sampling. The independent variables included clinical characteristics such as duration of illness, cancer stage, treatment received, treatment frequency, comorbidities, body mass index (BMI), and family history of cancer, while the dependent variable was QoL. QoL was assessed using the Indonesian version of the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (EORTC QLQ-C30), a validated instrument for evaluating functional status, symptoms, and global health status among cancer patients. QoL is categorised into poor, moderate, and good. Bivariate analysis was performed using Fisher’s exact test and the chi-square test. Results: Among the 53 breast cancer patients, the majority had been diagnosed for less than one year (45.3%), underwent surgery combined with chemotherapy (41.5%), and received treatment every three weeks (64.2%). Most patients reported moderate global health status (49.1%), while 35.8% had poor QoL. Significant associations were found between duration of illness (p < .001; Cramer’s V = 0.467), treatment received (p = .030; Cramer’s V = 0.434), and treatment frequency (p = .034; Cramer’s V = 0.396) and global health status. No significant associations were identified between cancer stage, comorbidities, BMI category, or family history of cancer and QoL. Conclusion: Duration of illness and treatment-related factors were significantly associated with quality of life among breast cancer patients. These findings suggest that the illness trajectory and treatment burden may be substantially related to patients’ overall well-being, supporting the need for targeted supportive care and routine QoL monitoring to improve patient-centred outcomes.